2008
DOI: 10.1093/carcin/bgn176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aurora-A suppresses epithelial–mesenchymal transition and invasion by downregulating MAPK in nasopharyngeal carcinoma cells

Abstract: Mitotic serine/threonine kinase Aurora-A (Aur-A) plays a critical role in regulating centrosome segregation and spindle assemble. Aur-A overexpression causes excessive centrosome duplication and abnormal spindle structure, leading to tumor malignant progression. Here, we investigated Aur-A expression in nasopharyngeal carcinoma (NPC) and the association between Aur-A and NPC invasiveness. We showed that overexpression of Aur-A in tumor tissues was correlated with cranial bone invasion and clinical stage in NPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 45 publications
5
98
2
Order By: Relevance
“…Thus, the development of more EGFR-like biomarkers, which not only act as prognostic factors but also as therapeutic molecules, would lead to the improvement of individualized medicine for locally advanced NPC. Our present study showed that, as well as being a therapeutic target, (33,37) Aurora-A was an independent prognostic factor for OS, PFS, as well as DMFS (Tables 2,3).…”
Section: P-valuesupporting
confidence: 52%
See 3 more Smart Citations
“…Thus, the development of more EGFR-like biomarkers, which not only act as prognostic factors but also as therapeutic molecules, would lead to the improvement of individualized medicine for locally advanced NPC. Our present study showed that, as well as being a therapeutic target, (33,37) Aurora-A was an independent prognostic factor for OS, PFS, as well as DMFS (Tables 2,3).…”
Section: P-valuesupporting
confidence: 52%
“…Although we previous proved that Aurora-A might to be a novel therapeutic target for NPC, (33,37) its prognostic value had not been defined. Here, we randomly selected 69 IC/RT patients as the training set and 75 IC/CRT patients as the testing set, that had comparable clinical features (Table 1) and survival probability (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study raises the possibility that Aurora kinase signals through the MAPK signaling pathway. There have been some reports indicating crosstalk between AURKA and MAPK [5,6]. As for the relationship between AURKB and MAPK, Kanda et al [7] showed that AURKB kinase activity was involved in Ras-mediated cell transformation.…”
mentioning
confidence: 99%